Exploring spatial entropy in the analysis of landscape pattern and ecological sustainability in watershed ecosystem. Issue 1 (1st March 2022) - Liu, X T; Zhao, H R
Abstract: Ecological sustainability research from the perspective of entropy has received extensive attention in recent years. Spatial entropy ( Hs ) is a new form of spatial heterogeneity analysis tool that applies entropy to distinguish and characterize different landscape patterns. In order to further explore the heterogeneity expression and ecological implication of Hs in the analysis of watershed ecosystem, this research takes Yanhe watershed as the study area. Based on the land use data of years 2000, 2010, and 2020, Hs in combination with 10 landscape metrics was applied for the study of landscape pattern and ecological sustainability. The results showed that: 1) Hs is correlated with landscape richness, aggregation and shape complexity, and it reflects the comprehensive heterogeneity information with high sensitivity to landscape variations, and also describes ecosystem stability with negative correlation; 2) The value of Hs showed a gradual increase from upstream to downstream in Yanhe watershed, and it dropped as a whole during the 20 years; 3) The stability of this basin from 2010 to 2020 had a greater variation range compared with the previous ten years, and the regions with large variation were mainly distributed in the midstream and downstream areas.